MOLECULARLY IMPRINTED POLY(METHYL RED) MODIFIED CARBON PASTE ELECTRODE FOR VOLTAMMETRIC DETERMINATION OF 3-BUTYLATED HYDROXYANISOLE - AMALIA RIYADI (NIM : 20513084), SANDRA
Butylated hydroxyanisole is a kind of synthetic phenolic antioxidant wich has two isomer: 3-tert-butyl-4-hydroxyanisole (3-BHA) and 2-tert-butyl-4-hydroxyanisole (2-BHA). Recently, the use of these synthetic phenolic antioxidants is not recomended by Ministry of Health because of the carcinogenic property of these compounds. Therefore, the use of these synthetic antioxidant is restricted in all kind of food. According to BPOM regulation No 38 Year 2013, the amount of synthetic antioxidant in food is limited to 200 mg/kg of sample. Therefore simple and accurate methods for BHA determination is needed. Many analytical proceedure for BHA determination have been developed based on spectrophotometry and liquid chromatography methods. However the reported methods for BHA determination required complex pretreatment step and the use a lot of organic solvent. Electrochemical techniques, such as voltammetry provides simple analytical procedure, low operational cost, good selectivity and high sensitivity. In this study, we developed a new molecularly imprinted polymer (MIP) modified carbon paste electrode (CPE) to increase the sensitivity of Butylated Hydroxyanisole (BHA) determination. Methyl red was electropolymerized on the surface of CPE with cyclic voltammetry technique (15 cycles) at potential range of -1,0V - 2,0V from solution containing methyl red and BHA in 0,1 M KNO3 as supporting electrolyte. To form the MIP, BHA was removed from polymer matrix by immersing the electrode in ethanol 30 second followed by 3 cycles of CV in 0,1 M KNO3 at potential range of 0,0V - 1,2V and scan rate of 100 mV/s. Linear Sweep Voltammetry (LSV) technique was used in BHA determination. Repeated measurement of 0.1 M BHA solution gave %RSD of oxidation peak of 8,8% (n=15). Calibration curve gave good linearity in the concentration range of 10 μM - 100 μM and 100 μM - 1000 μM with different slopes and limit of detection of 10,62 μM. Determination of BHA in margarine samples resulted in percent recovery between 96,96 - 103,50% which indicates good accuracy of the methods.